Lactate dehydrogenase and the severity of adenoviral pneumonia in children: A meta-analysis - Zou, Min; Zhai, Yang; Mei, Xiaoping; Wei, Xing (Frontiers in Pediatrics, 2023)
Background Children with severe adenoviral pneumonia (ADVP) have poor prognosis and high risk of mortality. We performed a meta-analysis to evaluate the association between pretreatment lactate dehydrogenase (LDH) and severity, postinfectious bronchiolitis obliterans (PIBO), and mortality in children with ADVP. Methods Relevant observational studies were identified by search of PubMed, Embase, Web of Science, Wanfang, and CNKI databases from inception to August 3, 2022. A random effect model was used to pool the results by incorporating the potential between-study heterogeneity. Results Overall, 23 studies with 4,481 children with ADVP were included in this meta-analysis. Results of meta-analysis showed that children with severe ADVP had a significantly higher level of pretreatment LDH as compared to those with non-severe ADVP (standard mean difference [SMD]: 0.51, 95% confidence interval [CI]: 0.36 to 0.66, p < 0.001; I2 = 69%). Besides, pooled results also suggested that the pretreatment LDH was significantly higher in children who developed PIBO as compared to those who did not (SMD: 0.47, 95% CI: 0.09 to 0.84, p = 0.02, I2 = 80%). Finally, results of the meta-analysis also confirmed that a higher pretreatment LDH (>500 IU/L) was a risk factor of increased mortality during hospitalization (odds ratio: 3.10, 95% CI: 1.62 to 5.92, p < 0.001, I2 = 0%). Sensitivity analyses by excluding one dataset at a time showed consistent results. Conclusion High pretreatment LDH may be associated with disease severity, development of PIBO, and increased risk of mortality in children with ADVP.